Wired and single sideband wireless service based on a single optical modulator - Weiping LI; Miao KONG; Yanyi WANG; Jianjun YU (Tongxin xuebao)
In order to provide more flexible and convenient service for users in the hybrid transmission network,a novel system using a single optical modulator to provide wired and single side band (SSB) wireless signal was proposed.By combining the application of dual-polarization binary phase shift keying modulator (DP-BPSK),phase shifter and other devices,wired and SSB wireless signals were directly generated to suppress the walk-off effect caused by dispersion,and the effective transmission of 5 Gbit/s SSB wireless signal carried on 40 GHz millimeter wave and 10 Gbit/s wired signal over 65 km single-mode fiber (SMF) were successfully achieved.The experiments show that the application of polarization multiplexing technology and optical subcarrier multiplexing technology can make the signal have a greater improvement in transmission rate and performance,and play an important role in the future broadband communication network.